2006
DOI: 10.1111/j.1468-1331.2006.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurobrucellosis as an exceptional cause of transient ischemic attacks

Abstract: We report a series of four cases presented with transient ischemic attacks (TIA) or ischemic stroke as the predominant manifestation of neurobrucellosis (NB). Three of the patients were 20–28 years of age, and one patient was 53 years old. They all used to consume unpasteurized milk or its products. Two patients had systemic brucellosis in the past and received antibiotic treatment. Other causes of TIA including cardiac embolism, hypercoagulability, vascular malformations, systemic vasculitis, and infective en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Several clinical forms of brucellosis affecting the CNS have been reported, including meningitis, meningoencephalitis, myelitis, radiculoneuritis, cranial nerve involvement, and demyelinating or vascular disease (3,4,6,7). Thus, the presentation of NB is diverse (6).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical forms of brucellosis affecting the CNS have been reported, including meningitis, meningoencephalitis, myelitis, radiculoneuritis, cranial nerve involvement, and demyelinating or vascular disease (3,4,6,7). Thus, the presentation of NB is diverse (6).…”
Section: Discussionmentioning
confidence: 99%
“…The third patient presented as meningitis which is the most clinical presentation of neurobrucellosis and meningovascular complications (8)(9)(10)13). His cranial MRI showed that meningeal enhancement with periventricular edema which seen on brain imaging in the early phase of brucellar meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobrucellosis is a rare complication of brucellosis and sometimes neurological symptoms may be the only symptoms. The criteria for definite diagnosis of neurobrucellosis are 1-neurological dysfunction not explained by other neurological diseases, 2-abnormal CSF indicating lymphocytic pleocytosis and increased protein, 3-positive CSF culture for Brucella organisms or positive Brucella IgG agglutination titer in the blood and 4-CSF, response to specific chemotherapy with a significant drop in the CSF lymphocyte count and protein concentration (4,5,8). We presented three different clinic forms of neurobrucellosis which fulfilled all the diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucellosis is clinically characterized by fever, joint pain, night sweats, weight loss and hepatosplenomegaly. It is generally believed that only 4% of the patients have neurological manifestations accompanying these symptoms [2][3][4][5]; these conditions vary widely and include polyradiculitis, myelopathy, encephalitis, or meningitis [6], brain or epidural abscess [7,8], injury of cranial nerve [3,[9][10][11], transient ischemic attack and other vascular diseases [12,13], altered mental status [14]. Parkinsonian-like tremor is rare.…”
Section: Introductionmentioning
confidence: 99%